For a sociology of academic work Job insecurity, teaching and research at the University - Castillo Alonso, Juan José; Moré Corral, Paloma (Sociología del Trabajo, 2016)
Higher education in Spain is in a constant process of transformation and this affects the teaching and research staff in their work and life. Our aim has been to deepen on the social problems experienced by researchers and teachers, identifying and analyzing the factors that determine and explain their strategies for dealing with academic career. We try to analyze their careers and labour strategies, academic and vital, so to understand, from his or her point of view, through their experiences, the transformations of the Spanish university system and the effects these have on the lives of those who undertake the academic career.
Keywords: work and life; casualization; academic career; professional career.